Nephroblastomatosis or Wilms tumor in a fourth patient with a somatic PIK3CA mutation. Issue 10 (18th May 2016) - Gripp, Karen W.; Baker, Laura; Kandula, Vinay; Conard, Katrina; Scavina, Mena; Napoli, Joseph A.; Griffin, Gregory C.; Thacker, Mihir; Knox, Rachel G.; Clark, Graeme R.; Parker, Victoria E. R.; Semple, Robert; et al.
Abstract : Wilms tumor and nephroblastomatosis are associated with syndromic conditions including hemihyperplasia. Hemihyperplasia is genetically heterogeneous and may be the result of genomic abnormalities seen in Beckwith–Wiedemann syndrome, mosaic chromosome or genomic abnormalities, or somatic point mutations. Somatic missense mutations affecting the PI3K‐AKT‐MTOR pathway result in segmental overgrowth and are present in numerous benign and malignant tumors. Here, we report a fourth patient with asymmetric overgrowth due to a somatic PIK3CA mutation who had nephroblastomatosis or Wilms tumor. Similar to two of three reported patients with a somatic PIK3CA mutation and renal tumors, he shared a PIK3CA mutation affecting codon 1047, presented at birth with asymmetric overgrowth, and had fibroadipose overgrowth. Codon 1047 is most commonly affected by somatic mutations in PIK3CA ‐related overgrowth spectrum (PROS). While the fibroadipose overgrowth phenotype appears to be common in individuals with PIK3CA mutations at codon 1047, individuals with a clinical diagnosis of Klippel–Trenaunay syndrome or isolated lymphatic malformation also had mutations affecting this amino acid. Screening for Wilms tumor in individuals with PROS‐related hemihyperplasia may be considered and, until the natural history is fully elucidated in larger cohort studies, may follow guidelines for Beckwith–Wiedemann syndrome, or isolated hemihyperplasia. It is not known if the specific PIK3CA mutation, the mosaic distribution, or the clinical presentation affect the Wilms tumor or nephroblastomatosis risk in individuals with PROS. © 2016 Wiley Periodicals, Inc.